Projects with a Very Long Life - Mackie, Peter; Nellthorp, John; Laird, James (World Bank, Washington, DC, 2012)
This note address issues considering: what types of project typically have a very long life? Section 1: discusses the choice of appraisal period; Section 2: analyses the use of residual values; Section 3: discusses the pitfalls to avoid; Section 4: looks at the sensitivity of these matters to the discount rate.